2016
DOI: 10.1007/s12192-016-0698-0
|View full text |Cite
|
Sign up to set email alerts
|

APL1, an altered peptide ligand derived from human heat-shock protein 60, increases the frequency of Tregs and its suppressive capacity against antigen responding effector CD4 + T cells from rheumatoid arthritis patients

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by a chronic relapsing-remitting joint inflammation. Perturbations in the balance between CD4 + T cells producing IL-17 and CD4 + CD25 high FoxP3 + Tregs correlate with irreversible bone and cartilage destruction in RA. APL1 is an altered peptide ligand derived from a CD4+ T-cell epitope of human HSP60, an autoantigen expressed in the inflamed synovium, which increases the frequency of CD4 + CD25 high FoxP3+ Tregs in peripheral blood mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Previously, we showed that CIGB-814 induced regulatory properties associated with inhibition of inflammation in several experimental models (Domínguez et al 2011;Barberá et al 2016;Lorenzo et al 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, we showed that CIGB-814 induced regulatory properties associated with inhibition of inflammation in several experimental models (Domínguez et al 2011;Barberá et al 2016;Lorenzo et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…This peptide increased the frequency of Treg and their suppressive capacity against antigen responding effector CD4 + T cells from RA patients. In addition, this peptide inhibits significantly IL-17 levels produced by effector CD4 + T cells from peripheral blood mononuclear cells (PBMCs) of RA patients (Kim et al 2016;Barberá et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the preclinical models, the peptide called APL1 was able to increase the percentage of CD4 þ CD25 þ FoxP3 þ Treg cells in vivo after inoculation into BALB/c mice and in the rat adjuvant arthritis model, where it was able to control histological damage and clinical signs of arthritis, an effect that was associated with increased proportions of FoxP3 þ Tregs in the spleen. Furthermore, the APL1 induced Tregs ex vivo in PBMCs obtained from RA patients [61].…”
Section: Development Of Hsp-based Immune Tolerance Therapiesmentioning
confidence: 96%
“…For instance, immunization with bacterial ( Mycobacterium tuberculosis ) or mammalian Hsp60 ameliorated or suppressed various experimental models of autoimmune diseases, e.g., adjuvant arthritis, collagen-induced arthritis, diabetes type I, or atherosclerosis in a Th2- and/or Treg-dependent way (van Eden et al 2005a , b ; Landstein et al 2015 ). Moreover, an altered peptide ligand (APL) derived from a CD4+ T cell epitope of human Hsp60 inhibited the course of murine arthritis, similarly to methotrexate (Lorenzo et al 2017 ), and increased the percentage of Treg or downregulated the secretion of pro-inflammatory IL-17 in peripheral blood mononuclear cell cultures from RA patients (Barberá et al 2016 ). Further, artificial induction of Hsp70 expression or administration of bacterial or murine Hsp70-derived peptides prevented inflammatory damage in experimental autoimmune arthritis models in a Treg- and/or IL-10-dependent way (van Eden et al 2005a , b ; Stocki and Dickinson 2012 ; Borges et al 2012 ; van Herwijnen et al 2012 ; van Eden et al 2013a , b ).…”
Section: Immunosuppressive Activity Of Hspmentioning
confidence: 99%